Gestão de agrotóxicos: uma proposta de controle para o Estado do Maranhão - MARQUES, Laura Antoniêta Araújo Soares (2017)
The State of Maranhão is a highlight in the agribusiness scenario as a major producer of grains, mainly soybeans. In spite of this, the state government still does not have an instrument that controls in detail the commercialization of these inputs. This gap allows the indiscriminate use of pesticides in crops, thus causing contamination of the environment and causing damage to human health. From the perspective of the consumption of agrochemicals, this paper presents as proposal a Computerized System to control the commercialization of pesticides in the State of Maranhão. The methodology used was the documentary research and bibliographic research on the consumption of pesticides in Maranhão, its main legal systems concerning the control of pesticides and analysis of the computerized systems implemented in some Brazilian states. As a result, a proposal is presented of a Computerized System to control the commercialization of pesticides in the State that allowed the registration of pesticides, the registration of commercial establishments and companies, the register of qualified professionals, agricultural producers and inspectors, the control of the movement of the entrance and exit of the products in Maranhão, through the release of the invoices. This system will become, therefore, essential instrument to the state organs, responsible for the control of the commercialization of pesticides.